Reverse Evidence: A Beacon of Hope for Pretrial Reform - Erwin Susilo; Artha Febriansyah; Dharma Setiawan Negara; Muhammad Rafi (Faculty of Law, Sriwijaya University, Indonesia, 2025)
Pretrial proceedings, inspired by the Habeas Corpus principle, aim to protect individuals from arbitrary coercive measures such as suspect identification, arrest, and detention. However, in practice, the burden of proof in pretrial processes falls entirely on the applicant, who must prove a negative: the illegality of the coercive action. This burden creates significant obstacles for applicants seeking redress. To address this imbalance, this research examines the concept of Habeas Corpus, the evidentiary system of reverse onus of proof in the Indonesian legal context, and the development of an ideal evidentiary model for pretrial proceedings. Using normative juridical methods, this study finds that Habeas Corpus obliges the detaining authority to justify the legality of detention; failure to do so results in the detainee's release. Similarly, reverse evidence has been applied in corruption, money laundering, and administrative cases in Indonesian courts to address challenges in uncovering organised crimes. In pretrial contexts, applying reverse evidence protects human rights, promotes transparency, and ensures accountability in the exercise of coercive state power. This approach reflects the legal principle that individuals should not be required to prove a negative, easing the applicant’s evidentiary burden. By shifting the burden of proof to the respondent (i.e., the state or its officers), it upholds the principle of equality of arms, creating a more balanced relationship between individuals and the state. Ultimately, this enhances safeguards against abuse of authority and improves fairness in the justice system.